The influence of team motivational climate on employee creativity—mediating role of domain-relevant skills - Zhao, Yanmei; Yu, Ting; Zhang, Zhengtang (Frontiers in Psychology, 2023)
Employee creativity drives enterprise development, and team motivational climate plays an important role in incubating employee creativity. Based on creativity component theory, this study explores the impact of team motivational climate (mastery climate and performance climate) on employee creativity and its mechanism. Through the paired data of supervisors and employees at three time points, the research shows that mastery climate positively affects employees' domain-relevant skills and domain-relevant skills positively affect employee creativity. By controlling the mediating effect of intrinsic motivation and self-efficacy, domain-relevant skills mediate the impact of mastery climate on employee creativity; performance climate and mastery climate work together on domainrelevant skills. When both are high, domain-relevant skills are highest. Performance climate moderate the mediating effect of domain-relevant skills between mastery climate and employee creativity. When performance climate is high, the mediating effect of domain-relevant skills is stronger. Suggestions for practice and future research are provided.